Development and Application of Multifunctional Optical Coherence Tomography - Zhi, Zhongwei (My University, 2014)
Microcirculation refers to the functions of capillaries and the neighboring lymphatic vessels. It plays a vital role in the pathophysiology of disorders in many clinical areas including cardiology, dermatology, neurology and ophthalmology, and so forth. It is crucial to develop imaging technologies that can provide both qualitative and quantitative information as to how microcirculation responds to certain injury and/or disease, and its treatment. Optical coherence tomography (OCT) is a non-invasive optical imaging technique for high-resolution cross-sectional imaging of specimens, with many applications in clinical medicine. Current state-of-the-art OCT systems operate in the Fourier domain, using either a broadband light source with a spectrometer, known as spectral domain OCT (SDOCT), or a rapidly tunable laser, known as swept source OCT (SSOCT). The current Fourier domain OCT systems have dramatically improvement in sensitivity, resolution and speed compared to time domain OCT. In addition to the improvement in the OCT system hardware, different methods for functional measurements of tissue beds have been developed and demonstrated. This includes but not limited to, i) Phase-resolved Doppler OCT for quantifying the blood flow, ii) OCT angiography for visualization of microvasculature, iii) Polarization sensitive OCT for measuring the intrinsic optical property/ birefringence of tissue, iv) spectroscopic OCT for measuring blood oxygenation, etc. Functional OCT can provide important clinical information that is not available in the typical intensity based structural OCT images. Among these functional OCT modalities, Doppler OCT and OCT angiography attract great interests as they show high capability for in vivo study of microvascular pathology. By analyzing the Doppler effect of a flowing particle on light frequency, Doppler OCT allows the quantification of the blood flow speed and blood flow rate. The most popular approach for Doppler OCT is achieved through analysis of the phase term in complex OCT signal which termed as Phase-resolved Doppler OCT. However, as limited by the phase noise and motion, Phase-resolved Doppler OCT can only be applied for relative large blood vessels, such as arterioles and venules. On the other hand, in order to visualize the microcirculation network, a number of strategies to enable better contrast of microvasculature components, which we termed OCT angiography, have been introduced during recent years. As a variation of Fourier domain OCT, optical microangiography (OMAG) is one of earliest proposed OCT angiography technique which is capable of generating 3D images of dynamic blood perfusion distribution within microcirculatory tissue beds. The OMAG algorithm works by separating the static and moving elements by high pass filtering on complex valued interferometric data after Fourier transform. Based on the conventional OMAG algorithm, we further developed ultra-high sensitive OMAG (UHS-OMAG) by switching the high-pass filtering from fast scan direction (adjacent A-lines within one B-frame) to slow scan direction (adjacent B-frames), which has a dramatically improved performance for capillary network imaging and analysis. Apart from the microvascular study with current available functional OCT for, visualization of the lymphatic system (lymph nodes and lymphatic vessels) plays a significant role in assessing patients with various malignancies and lymphedema. However, there is a lack of label-free and noninvasive method for lymphangiography. Hence, a cutting edge research to investigate the capability of OCT as a tool for non-invasive and label-free lymphangiography would be highly desired. The objective of my thesis is to develop a multiple-functional SDOCT system to image the microcirculation and quantify the several important parameters of microcirculation within microcirculatory tissue beds, and further apply it for pre-clinical research applications. The multifunctional OCT system provides modalities including structural OCT, OCT angiography, Doppler OCT and Optical lymphangiography, for multi-parametric study of tissue microstructure, blood vessel morphology, blood flow and lymphatic vessel all together. The thesis mainly focus on two parts: first, development of multi-functional OCT/optical microangiography (OMAG) system and methods for volumetric imaging of microvasculature and quantitative measurement of blood flow, and its application for pathological research in ophthalmology on rodent eye models; second, development of ultra-high resolution OCT system and algorithm for simultaneous label free imaging of blood and lymphatic vessel, and its application in wound healing study on mouse ear flap model. Objectives of my research are achieved through the following specific aims: Aim 1: Improve the sensitivity of OMAG for microvasculature imaging; perform volumetric and quantitative imaging of vasculature with combined OMAG and Phase-resolved Doppler OCT for in vivo study of vascular physiology. Aim 2: Develop high speed high resolution OCT system and method for rodent eye imaging. Apply the combined OMAG and Phase-resolved Doppler OCT approach to investigate the impact of elevated intraocular pressure on retinal, choroidal and optic nerve head blood flow in rat eye model, which aids to the better understanding of the mechanism and development of glaucoma. Aim 3: Apply the developed OCT system and ultra-high sensitive OMAG algorithm for noninvasive imaging of retinal morphology and microvasculature in obese mice, which may play an important role in early diagnosis of Diabetic retinopathy. Aim 4: Developing an ultra-high resolution SDOCT system using broadband Supercontinuum light source to achieve ultra-high resolution microvasculature imaging of biological tissue. Aim 5: Develop methods for simultaneous label free optical imaging of blood and lymphatic vessel and demonstrate its capability by monitoring the blood and lymph response to wound healing on mouse ear pinna model.
Thesis (Ph.D.)--University of Washington, 2014
Keywords: Biomedical Optics; Blood flow; Ophthalmology; Optical coherence tomography; Optical Imaging; Optical Microangiography; Biomedical engineering; Medical imaging and radiology; Optics; bioengineering